Efforts of Elementary Schools in Realizing Children-Friendly Schools in Gununganyar District, Surabaya - Agus Syairofi; Mohammad Affan (Attanwir : Jurnal Keislaman dan Pendidikan, 2026)
This research aims to explore the efforts of elementary schools in the Gununganyar District of Surabaya in realizing child-friendly schools. This study is a descriptive qualitative research. The research methods used are interviews, documentation, observation, and analysis of articles from the sampled school's website. The data's validity is checked using triangulation technique, where the obtained data is confirmed integratively. Based on the research results, primary schools in the Gununganyar District of Surabaya are making several efforts to create child-friendly schools, such as implementing a child-friendly curriculum, creating a safe and comfortable environment, establishing child-friendly policies and rules, involving parents and the community, and developing child development programs. One example of a child development program implemented by some schools is conducting regular religious activities and maximizing students' potential in academic and non-academic fields, among other things. It is expected that with these efforts, schools in Surabaya can continue to improve their quality and become more child-friendly. Moreover, it requires synergy among schools, parents, and the community to create a safe and comfortable environment for children.